Hemipteran and dipteran pests: Effectors and plant host immune regulators. Issue 4 (1st December 2015) - Kaloshian, Isgouhi; Walling, Linda L.
Abstract: Hemipteran and dipteran insects have behavioral, cellular and chemical strategies for evading or coping with the host plant defenses making these insects particularly destructive pests worldwide. A critical component of a host plant's defense to herbivory is innate immunity. Here we review the status of our understanding of the receptors that contribute to perception of hemipteran and dipteran pests and highlight the gaps in our knowledge in these early events in immune signaling. We also highlight recent advances in identification of the effectors that activate pattern‐triggered immunity and those involved in effector‐triggered immunity. Abstract : In this review we address the status of our understanding of the early events in plant host innate immune signaling against hemipteran and dipteran insects. We also highlight recent advances in identification of insect effectors from these taxa that affect immunity.